# MATH TROUBLES HELP ME PLEASE (ALGEBRA 2)?

So, I gotta solve for x and I'm stuck with these problems??

1. -18x = 4x - 11

2. 34 + 16 = 5x + 10

3. 23- 2x = 15 - x

4. -2 (1 - x) + 4x = -3

i really need help so please help me?

i'd appreciate if you'd show how you did it?? like its great if you give answers but i'd actually like to learn lmao

### 4 Answers

- Anonymous8 years agoFavorite Answer
1)

-18x = 4x - 11

To make it nicer, +11 to both sides (all steps must be done on both sides of the = sign)

-18x + 11 = 4x + 0

Add 18x to both sides

0 + 11 = 4x + 18x

Neaten:

11 = 22x

Divide by 22

1/2 = x

2)

34 + 16 = 5x + 10

(I feel like that should have an x on the LHS somewhere?)

Three choices, then:

34 + 16 = 5x + 10

Add 34 + 16:

50 = 5x + 10

-10 from both sides:

40 = 5x + 0

Divide by 5:

8 = x

If instead it should be:

34 + 16x = 6x + 10

-10 from both sides:

24 + 16x = 6x

-16x from both sides:

24 = 6x - 16x

Neaten:

24 = -10x

Divide by -10

-2.4 = x

Or if it should be 34x + 16 = 5x + 10

-16 from both sides:

34x = 5x - 6

-5x from both sides:

29x = -6

divide by 29 (which I'm not going to do in my head...)

3) 23 - 3x = 15 - x

-15 from both sides

8 -3x = -x

+3x to both sides

8 = -x + 3x

Neaten:

8 = 2x

Divide by 2:

4 = x

4) -2(1-x) + 4x = -3

First, deal with the bracket by multiplying out:

-2(1) + (-2)(-x) + 4x = -3

-2 +2x +4x = -3

Neaten:

-2 + 6x = -3

+2 to both sides:

6x = -3+2

6x = -1

Divide by 6:

x = -1/6

Hope that clears it up a bit! :)

- Login to reply the answers

- Anonymous8 years ago
(1) -18x = 4x - 11

When you move numbers from one side to the other, you have to change the signs. Therefore:

-18x - 4x = -11

-22x = -11

To find x, you have to get rid of the coefficient and the negative. Therefore:

x = -11 / -22

= 1/2

(2) 34 + 16 = 5x + 10

50 = 5x + 10

Same thing as what I said before. When I move a number over, I have to change the signs:

50 - 10 = 5x

40 = 5x

Likewise as what I did earlier.

40/5 = x

8 = x

This is the same as writing: x = 8.

(3) 23 - 2x = 15 - x

Nothing new here....you do the same as what we've done previously.

-2x + x = 15 - 23

-x = -8

Divide both sides by '-1'.

x = 8

(4) -2(1-x) + 4x = -3

You expand the equation:

-2(1) - -2(x) + 4x = -3

-2 + 2x + 4x = -3

6x = -3 + 2

6x = -1

x = -1/6

--------------------------------

I hope this helps! :) If you don't understand you should ask your teacher or someone who could go through it with you.

- Login to reply the answers

- 8 years ago
1.) -18x = 4x - 11 balance this out like a scale. whatever you do to one side must be done to the other

-18x + 11 = 4x Add 11 to each side to get rid of the -11

11 = 22X add 18x to each side to get rid of the -18x

x = 2 divide by 11

2.) 34 + 16 = 5x +10

40 = 5x + 10

30 = 5X

x = 6

3.) 23 - 2x = 15 - x

23 = 15 + x

8 = x

4.) -2(1-x) + 4x = -3

-2 +2x + 4x = -3

-2 + 6x = -3

6x = -1

x = -.167

- Login to reply the answers